Nest Association between Camponotus fallax (Hymenoptera: Formicidae) and Vespa crabro (Hymenoptera: Vespidae) in Central Iberian Peninsula - Mora-Rubio, Carlos; Pérez-Bote, José Luis; Muriel, Jaime (Sociobiology, 2019)
Because social wasps often defend their nests by inflicting painful stings or bites, some animals associate with them looking for protection against potential predators. Some neotropical vespids are known to maintain associations with other insect and vertebrate taxa, such as birds and bats, however there are not previous records about associations between ants and hornets in Europe. In this study, we reported the first case of association between the arboreal ant Camponotus fallax and the European hornet Vespa crabro in Europe. The observations were made in Central Spain, where two colonies of C. fallax were found in two different avian nest-boxes inhabited by V. crabro when spotless starlings finished their breeding season. The reasons of this possible association are also discussed.